The integration of LARG supply chain paradigms and supply chain sustainable performance (A case study of Iran). Issue 1 (1st January 2021) - Anvari, A.R.
ABSTRACT: This research aims to conduct whether the lean, agile, resilience, green and sustainable paradigms are applied and combined in the actual environment (Petrochemical Industries) of Supply Chain Management (SCM). A structured literature review of theoretical foundations of manufacturing paradigms in SCM was carried out to achieve this aim. Then the conceptual model is extracted from reviewing theoretical research foundations and structure of 'Lean, Agility, Resilience, Green' (LARG) supply chain and sustainability. The novelty of this research is that a classification scheme of manufacturing paradigms in SCM was developed where previous studies were used to find how these paradigms were being integrated. The results indicated that paradigms in SCM, including; Lean, Agile, Resilience, Green, and Sustainable had an important role in the successful performance and competitive advantage. The Goodness of Fit was used to examine the verification model solution. The contribution of this research is an integrated model of LARG supply chain paradigms and sustainable supply chain performance. The proposed model is merged in academic literature for the first time. The integration model of LARG supply chain paradigms and supply chain sustainable performance